Livraria “independente” na era digital: um estudo de caso da Barsa Livros como rugosidade - Bottaro, Thiago Barsalobres (Universidade Federal de São Carlos, 2025)
In order to formulate its basic hypothesis, this research starts from the following question: does Barsa Livros, an independent bookstore, present itself as an element of friction [rugosidade] within the dynamics of vertical and horizontal relationships of the social organization? Barsa Livros is an independent bookstore in Ribeirão Preto, state of São Paulo, Brazil. It began its activities in 2020, initially operating digitally and with a sales system based on orders. As it developed, it adopted a hybrid approach: dealing with printed books and building its inventory; participating in fairs held in various cultural spaces; and, subsequently, also establishing a physical location, where its activities now take place and where its entire collection is housed. Through a case study, we propose to analyze the publishing market – notably the bookselling sector – in its current historical particularity, with the presence of digital technology and the power exerted by the use of information, presented within the empirical framework of John B. Thompson (2021) and through Bourdieu's (2018) field theory, in order to define the publishing and bookselling field and position the studied bookstore within it. Furthermore, in light of José De Souza Muniz Júnior's thesis (2016), we will study the position of "independent" within this publishing field, as well as the polysemy of the term and its possible characteristics in order to understand the possibility of Barsa Livros presenting itself as an independent bookstore in this field. Subsequently, using Milton Santos' geographical theory (2023), the dynamics of verticalities and horizontalities that compose the banal space will be analyzed in order to verify whether Barsa Livros presents itself as an element of friction within it. Finally, we will test the hypothesis that this bookstore functions as a medium and materializes this friction in space through the methodology of materialized organization and organized matter (OM/MO) as seen in Régis Debray (2000), in addition to analyzing the bookstore's collection as a technema: a technique that makes it point to reticular and/or contiguous organizations, as well as, in its double-body, relate to hegemonic and/or popular sensibilities (Santos, 2022).
"Independent" bookstore on digital age: a case study of Barsa Livros as a rugosity
Keywords: Rugosidade; Livraria independente; Espaço banal; Técnicas; Globalização; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA; 8. Trabalho Decente e Crescimento Econômico